Consecuencias que ha Causado el Divorcio en el Área Emocional y Conductual en los estudiantes en una Institución Educativa del Distrito Turístico, Especial y Cultural de Riohacha (2022)
Within the present investigation we find a topic that has always been of great relevance at a social level and that is divorce and the consequences on children, which is why the main objective was to know the consequences in the emotional and behavioral area that has caused divorce in children, to carry out this study a population of the Jose Antonio Galán Educational Institution located in the city of Riohacha, La Guajira-Colombia was chosen. A mixed research method was chosen, with a descriptive scope, and the application of two instruments was carried out, first a survey of 12 questions with Likert-type answers was carried out, and then a projective test was applied (the Test of the drawing of the family by Corman). To carry out this research, there was a sample of 37 students from 5th and 6th grades. Within the results obtained, distraction is one of the most common behaviors when carrying out an academic activity, it is also evident within the behaviors of these in their homes according to the results that they are mostly disorganized children and that they do not They really like to collaborate in basic household chores, that they don't really like to comply with the rules and norms designated by their parents, in this case with whom they live, also that they don't know how to control their anger when something bothers them since this leads them to have behaviors like hitting or throwing things, and disrespecting their elders with offensive words.